(untitled) (Journal of Parents and Teachers, 2014)
This article, number eighth of the series “Music and more music” presents blues as a musical style. It talks about the history, the sociocultural context in which it was born, the aim of this music style, the musical characteristics and the main bands and singers. The author chooses a band to work with in the class, and this is The Notting Hillbillies and its song “Railroad worksong” to analyze musically and from an ethic and citizenship point of view.